AAGBS welcomes Cardiff University Delegates - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
The faculty is thrilled to host esteemed delegates from Cardiff University. United Kingdom, at the Arshad Ayub Graduate Business School (AAGBS) after their visit at UiTM's Vice Chancellor's office. The delegates arrived for discussions and collaborations with faculties from UiTM. The faculties of UiTM involved were the Faculty of Business and Management, College of Creative Arts, Faculty of Law, Faculty of Computer Science and Mathematics, College of Engineering. and Arshad Ayub Graduate Business School. The discussion developed a sense of excitement as the potential joint activities would help shape the future of education and research.